2005
DOI: 10.1161/01.hyp.0000172623.36098.4e
|View full text |Cite
|
Sign up to set email alerts
|

Differing Administration Time-Dependent Effects of Aspirin on Blood Pressure in Dipper and Non-Dipper Hypertensives

Abstract: Abstract-Aspirin is a potent antioxidative agent that reduces vascular production of superoxide, prevents angiotensin II-induced hypertension, and induces NO release. Low-dose aspirin administered at bedtime, but not on awakening, has also been shown to reduce blood pressure, possibly enhancing the nocturnal trough in NO production. Because endothelium-dependent vasodilation is blunted through a decrease in NO release in non-dipper compared with dipper patients, we compared the administration time-dependent in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
53
1
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(58 citation statements)
references
References 46 publications
3
53
1
1
Order By: Relevance
“…22,23 On the other hand, Hermida et al reported an inverse association between aspirin intake (100 mg/day) given before bed-time and mean 24 hour BP levels (-6/-4 mm Hg reduction of systolic BP/ diastolic BP) 10 especially in non-dippers. 11 24 Two meta-analyses assessing the association of aspirin and other NSAIDs with BP levels have been published. The first meta-analysis found that among a total of 771 participants, NSAIDs increased mean blood pressure by 5 mm Hg overall (95% CI, 1.2-8.7).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…22,23 On the other hand, Hermida et al reported an inverse association between aspirin intake (100 mg/day) given before bed-time and mean 24 hour BP levels (-6/-4 mm Hg reduction of systolic BP/ diastolic BP) 10 especially in non-dippers. 11 24 Two meta-analyses assessing the association of aspirin and other NSAIDs with BP levels have been published. The first meta-analysis found that among a total of 771 participants, NSAIDs increased mean blood pressure by 5 mm Hg overall (95% CI, 1.2-8.7).…”
Section: Discussionmentioning
confidence: 99%
“…4 Results from different prospective studies conducted in the United States assessing the association between use of aspirin, NSAIDs and other analgesics and the risk of hypertension suggest that chronic users of aspirin, NSAIDS, and acetaminophen have a higher risk of hypertension. [5][6][7][8][9] However, some clinical trials conducted in Spain have shown the opposite effect 10,11 and no previous prospective study has assessed this potential relationship in a European cohort, where a different health system probably means different access to medication and a different pattern of drug use. 12 Our objective was to assess the association between regular use of aspirin and non-aspirin analgesic drugs and the incidence of HTN in a prospective dynamic cohort study consisting of Spanish university graduates, the SUN (Seguimiento Universidad de Navarra, University of Navarra Follow-up) project.…”
Section: Assessment Of Incident Hypertensionmentioning
confidence: 99%
“…Subjects were eligible for participation if they had an untreated grade 1 hypertension, defined as systolic blood pressure between 140 and 159 mm Hg and/or diastolic blood pressure between 90 and 99 mm Hg, 1 and were Ͼ18 years old and capable to give informed consent, which are the same inclusion criteria as used by Hermida et al 8,9 Subjects were excluded if they had grade 2 or 3 hypertension (blood pressure Ն160/100 mm Hg), evidence of secondary arterial hypertension, any history of cardiovascular disease, diabetes mellitus, or rheumatoid arthritis or known contraindications to the use of aspirin (defined as history of asthma, any bleeding disorder, gastrointestinal tract bleeding, or known allergy to acetylsalicylic acid). Other exclusion criteria were severe renal or hepatic dysfunction, pregnancy, concurrent participation in other research projects or blood donation, and use of blood pressure-lowering medication, nonsteroidal anti-inflammatory drugs, or anticoagulant medication.…”
Section: Subjectsmentioning
confidence: 99%
“…3 Notably, in studies addressing this association, it was not reported at what time of the day aspirin was ingested by the participants. [5][6][7] In contrast, 2 recent randomized, controlled trials by Hermida et al 8,9 have shown that 100 mg of aspirin strongly decreased blood pressure in subjects with grade 1 essential hypertension when it was administered at bedtime, whereas (if anything) blood pressure might be slightly increased when aspirin was taken on awakening. In the subjects allocated to aspirin at evening, reductions of systolic and diastolic blood pressures of, respectively, 7.2/4.9 and 6.8/4.6 mm Hg (systolic/diastolic blood pressure) were recorded, whereas in the participants using aspirin at morning, a slight elevation of, respectively, 1.5/1.0 and 2.6/1.6 mm Hg was observed.…”
mentioning
confidence: 98%
See 1 more Smart Citation